Dilema Kekerasan dalam Ayat-ayat Kitab Suci - Eko Riyadi, Staniselaus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2019)
Violence is a crime condemned by religions, but religions in the world are apparently involved in some kind of violence. It has been considered problematic that some scriptural texts are showing violent acts that seem to be ‘authorised’ by God, even ‘allowed’ by God, or celebrated by the people. How should we understand such problematic texts? Is there any violence authorised by God? Christianity has been dealing with the interpretation of violent acts in biblical texts from the Old Testament as well as from the New Testament. This article suggests that violence in the biblical texts must be understood within the context of defining religious identity of Israel among the other nations that have their own gods. Scriptures do not promote violence, but has recorded the historical experiences of Israel in their confrontation with other nations. Therefore, violence in the biblical texts cannot be referred to as a sort of justification for any violent acts by religions in our multireligious and multiethnic society.